Quality teacher nation's aspiration : expectation vs. reality - Hamzah, Mohd Sahandri Gani; Abdullah, Saifuddin Kumar (EuroJournals, 2009)
Education in Malaysia is on-going efforts towards further developing the potential of individuals in a holistic and integrated manner, so as to produce individuals who are intellectually, spiritually, emotionally and physically balanced and harmonic, based on a firm belief in and devotion to God. Such an effort is designed to produce Malaysian citizens who are knowledgeable and competent, who possess high moral standards and who are responsible and capable of achieving high level of personal well-being as well as being able to contribute to the harmony and betterment of the family, the society and the nation at large. Effective teachers are repeatedly listed as fair, democratic, respectful, caring, consistent and good listeners. They are stimulating, creative and confident. They know the students both academically and personally. They have knowledge of what they teach and model strategies of good instruction. However, the quality of teachers in our country is being questioned. The requirements to be a teacher are not standardized. Moreover, there are some of the remark made with regards to our teachers are not very flattering, they have included being "very poor in communication, disinterested in teaching and look down to their peers as well as being of poor quality because the new recruits are that of graduates who were not able to seek employment elsewhere." Over the last 5-8 years, many colleagues have been converted to universities in the country in a bid to improve the "quality of education" and increase the number of degree graduates. What the conversion has managed to do is to successfully increase the number of degree graduates but without being able to significantly improve the quality of education. Hence we are getting diploma graduates masked as degree holders.